Extent of availability of major nutrients from selected Cereal Crop Residues to dairy ruminants as an alternative Dry Season Forage in Northern Uganda. - Geofrey, Nviiri; Okello, H.; Nakyewa, P.; Maiteki, G. A. (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
This work aimed at determining the availability of major nutrients from cereal crop residues (CRs) of maize, rice and sorghum to dairy ruminants in Northern Uganda. The major nutrient composition of the CRs was determined to establish their potential as alternative dry season forage resources for dairy animals. The CRs were selected based on crop economic importance and availability at the on-set of the dry season in randomly selected sub-counties of Lira, Otuke and Kole districts. Five samples of each CR were obtained from 20 farmer’s fields immediately after harvesting of each crop. Chemical analyses measured included Dry matter (DM), Crude protein (CP), Acid detergent fiber (ADF), Neutral detergent fiber (NDF), Digestible energy (DE), Organic matter digestibility (OM dig), Calcium (Ca), and Phosphorous (P). Fresh maize stover (MSF) had the highest CP (70.5g/kg DM), DE (11.3 MJ/kg DM), and lowest lignifications (49g/kg DM). Rice straw (RS) had a CP (42.1g/kg DM), lowest DE (6.9MJ/kg DM) and OM dig (506 g/kg DM). Dry maize stover (MSD) had the highest lignifications (76.0 g/kg DM) and low OM dig (543 g/kg DM) and sorghum stover (SS) had the lowest CP (40.0 g/kg DM) and a very low DE (7.1MJ/kg DM). The low CP levels and high levels of lignification limit the digestibility of the CR. However, their CF digestibility can be improved using an energy rich by-product, molasses (12.7MJ/kg DM) while the CP limitation due to ligfications can be improved through urea treatment.